Botox® for chronic anal fissure: is it useful? A clinical experience withmid-term follow-up - Piccinni, G.; Poli, E.; Angrisano, A.; Sciusco, et al., A. (Acta Biomedica Atenei Parmensis, 2009)
Background: Sphincterotomy has been the most commonly used treatment for chronic anal fissures. Although effective it is associated with incontinence (0-20%). Intrasphincteric Botulinum Toxin A injection seems to be a reliable option. The aim of this clinical report is to verify the effectiveness of this treatment in relieving symptoms and healing fissures without relapse. Methods: The study design was an open label non-comparative prospective trial to evaluate the efficacy of botulinum toxin injection in anal sphincters. In the period 2003-2005 sixty patients were enrolled in our Unit of Coloproctology. After inoculation hygiene measures (sitz baths, Vaseline oil and water intake) were recommended. After the first 4 weeks without improvement we administered a second injection (30 U.I). After failure of the second administration the patient was addressed to surgery. Mean follow-up was 24 months; patients were re-evaluated at the 6th, 12th and 24th month. Results: In 29 pts the fissure was healed (48.33%) after the first injection; 31 patients (51.6%) were re-treated; 20 pts presented a complete healing of the fissure in a period ranging between 4-5 weeks from the second injection and 11 patients were introduced to surgery. In 3 cases we observed haemorrhoidal thrombosis. Gas incontinence was reported in two patients and solved spontaneously. Conclusions: Our clinical experience suggests that botulinum toxin therapy can be considered effective and safe. It can be proposed to the patient as first line therapy before surgery.